930-P: Advanced Hybrid Closed-Loop System Is Associated with Increase in Tighter Glycemic Range—One-Year Observational Study - RIZZI, ALESSANDRO; TARTAGLIONE, LINDA; LAURA LEO, MARIA; LUCACCINI PAOLI, LORENZO; TOSTI, GIULIA; POPOLLA, VALENTINA; PITOCCO, DARIO (Diabetes (New York, N.Y.), 2023)
Background and Aims: Advanced hybrid closed loop systems (AHCL) are associated with improvement of HbA1c and time in range (TIR). However AHCL give the possibility to gain even tighter glycemic control. Thus, the aim of this study was to evaluate the efficacy of AHCL to increase time spent in tighter glycemic range (TR, 70-140 mg/dl) and to assess any difference between younger and older subjects. Methods: In an observational retrospective single center study, adults with T1DM using AHCL with predictive integrative derivative (PID) algorithm were enrolled. All participants were recruited at Diabetes Care Unit - Fondazione Policlinico Agostino Gemelli in Rome (IT). Data about TR and standardized metrics have been collected before starting AHCL and 3, 6, 9 and 12 months after AHCL initiation. We compared TR variation over time between younger (age <65 years) and older (≥65 years) subjects. Change in TR over time was evaluated with a linear mixed-effect model including age-group and presence of diabetic complications. Results: We enrolled 75 subjects with T1DM, age 50.5 (14.2) years [mean (standard deviation)], 35 females (46%), duration of disease 24.7 (13.3) years. 17 subjects (23%) were older and 58 (77%) were younger. 39 (52%) subjects were already using an insulin pump before starting AHCL and 36 (48%) were on multiple daily injections. HbA1c before AHCL was 7.6 (0.98) and 12 months after ACHL was 7.2 (0.6) (p=0.03). TR significantly increased over 12 months in the overall populations (TR before AHCL 37.6% (15.3) vs TR 12 months 52.9 % (12.8), p<0.001). Age or presence of complications did not affect the improvement of TR (p=0.38). TR 50% corresponded to mean TIR 76.2% Conclusions: AHCL is associated with significant improvement in tighter glycemic control. This improvement is not different between younger and older subjects. AHCL is an effective and safe system to aim to strict metabolic control in all subjects with T1DM.